MIDWIFERY CARE OF DELIVERY WITH CHRONIC HYPERTENSION SUPERIMPOSED PREECLAMPSIA AND UTERINE MYOMA (CERVICAL) - Ivon Diah Wittiarika; Gitta Arinda Faustina; Zukhrufatin Zukhrufatin (UNIVERSITAS AIRLANGGA, 2022)
Background: the most common causes of maternal death in Indonesia are hypertension/pre-eclampsia/eclampsia, bleeding, and infection. Hypertension in pregnancy ranks first as the cause of death in Indonesia at 33% (SRS Litbangkes, 2016). Cervical fibroids can cause complications in both pregnancy and childbirth. The purpose of this case report is to study midwifery care in complex cases. Case report: A 41-year-old woman, second pregnant, 36-37 week’s gestation, primipaternity, secondary primitua with chronic hypertension and uterine myoma (cervical) was referred to the hospital for delivery. Management focuses on support for the mother, involving the family, fulfill the needs of the mother, collaboration with the doctor conducting informed consent regarding the diagnosis, providing counseling and health education on tubectomy contraception, and accompanying the mother until the time of surgery. The mother's response is good, and optimistic about her condition and the baby. Conclusion: midwives in providing midwifery care in cases of delivery with chronic hypertension, superimposed preeclampsia and uterine myoma at an advanced health facility (Type A Hospital). Midwifery care is provided both independently and in collaboration with other professions. Delivery was carried out by caesarean section in accordance with the indications with the output of the mother and baby being healthy. Early detection, recognition of signs and symptoms, diagnosis, referral process and comprehensive management are carried out appropriately.